Molecular Identification and Antibacterial Evaluation of Bacillus thuringiensis Isolated from Soil Samples in Central Iraq - Al-Rammahi, Ameer Abood Karim; Alkhazraji, Enas k. (American Journal of Bioscience and Clinical Integrity, 2026)
Bacillus thuringiensis is an environmental bacteria found in many environments that have the ability to produce highly effective proteotoxins that can be used as an antibacterial pathogen. During this study, 50 soil samples were collected from four governorates of Baghdad, Babylon, Najaf, and Karbala. The soil was treated with 0.85% NaCl and then exposed to a temperature of 80 °C to obtain the spores and kill of other bacteria associated with Bacillus in the soil. 0.5-1 ml of suspended broth was taken and incubated with LB broth incubated for 6-16 hours to reduce the growth of bacteria, and then dilution were applied to bacterial growth and cultured in different media to diagnose the bacteria microscopicly and biochemically, including Hichrome Bacillus agar medium, where the bacteria appeared blue and the medium color was yellow, which indicates that they ferment menthol and produce the enzyme glycosidase. The general characteristics of the bacteria were then studied, as it was a mobtle bacillus producing spores, beloved to catalysis, methyl red, negative to oxidase, and to assay indole, degrading starch, and strong positive for lecithinase, fermented for glucose and menthol and hemolysis of Blood. It was genetically diagnosed based on the specific 16sRNA, then BT toxin was extracted after stimulating the bacteria to produce spores on nitrogen poor media, collecting the spores, extracting the cry protein(Bt toxin) with a weight 2µg-0.5mg, and testing its ability as an antibacterial, as it showed high effectiveness against the pathogenic bacteria and a minimum inhibitory concentration was 0.15 µg against Gram-positive pathogenic bacteria and 0. 31 µg against Gram-negative bacteria.